Delayed Emergence From Anesthesia: A Simulation Case for Anesthesia Learners - Terry A. Ellis; Jordan Louis Edberg; Nakul Kumar; Daniel James Applefield (Association of American Medical Colleges, 2017)
Introduction Delayed emergence is failure to regain consciousness following general anesthesia. It commonly involves altered mental status and respiratory compromise leading to increased morbidity, operating room delays, and increased cost. Causes include residual anesthetics, pharmacologic actions, surgical complications, neurologic events, endocrine disturbances, and patient-related factors. Pseudocholinesterase deficiency is an important consideration in delayed emergence. These patients are unable to effectively metabolize the muscle relaxants succinylcholine and mivacurium, leading to prolonged paralysis following administration. Methods This simulation exercise is designed for medical students, student nurse anesthetists, and resident physicians. It is a 1-hour small-group learning activity centered upon a single patient encounter. We employ this exercise using an anesthesiology resident physician to proctor, a simulation technician to program and run, and a faculty anesthesiologist to mentor each session. It is intended to reinforce required reading assignments and improve the approach to delayed emergence from anesthesia. The debriefing includes discussion of risk-reduction strategies for incorporation in clinical practice. This exercise is easily reproduced using modern simulation mannequins without specialized programming. Results Learners provided evaluations of their experience participating in the exercise, and resident physicians evaluated their experience proctoring the sessions. Responses were positive, and constructive criticism led to modifications to the exercise after development. Discussion We use this exercise as an educational opportunity for medical students rotating clinically in our department. Medical students are paired with resident physicians for scenario development and work with faculty to produce valuable educational activities that benefit the entire department.